Membraneless organelles: phasing out of equilibrium. Issue 3 (11th December 2020) - Hondele, Maria; Heinrich, Stephanie; De Los Rios, Paolo; Weis, Karsten
Abstract : Over the past years, liquid–liquid phase separation (LLPS) has emerged as a ubiquitous principle of cellular organization implicated in many biological processes ranging from gene expression to cell division. The formation of biological condensates, like the nucleolus or stress granules, by LLPS is at its core a thermodynamic equilibrium process. However, life does not operate at equilibrium, and cells have evolved multiple strategies to keep condensates in a non-equilibrium state. In this review, we discuss how these non-equilibrium drivers counteract solidification and potentially detrimental aggregation, and at the same time enable biological condensates to perform work and control the flux of substrates and information in a spatial and temporal manner.